The Use of the Greeting ”Yang” as a Form of the Maxim of Appreciation in the Surabaya Traditional Market - Syaida, Rury Amrilatus; Indrayanti, Tri; Budiyono, Sunu Catur (Universitas Muria Kudus, 2024)
Language politeness is how to maintain one’s speech when communicating so as not to offend other people’s feelings. This research aims to describe the use of the greeting ”yang” as an application of the maxim of appreciation in traditional markets in Surabaya. The markets chosen to be research objects are Pucang Market, Pagesangan Market, Turi Market, Manukan Market, and Genteng Market. This research applies Geoffrey Leech’s politeness thepry. The research approach used is a qualitative approach with observational data collection techniques, determining markets, visiting designated markets, preparing recording equipment, visiting kiosks, recording people’s speech, and transcribing data. The data analysis technique uses descriptive methods. From the research results, it can be concluded that the results of data analysis amount to seven utterances that use the greeting ”yang” in the Surabaya traditional market. The purpose of using the greeting ”yang” in social interactions in traditional markets in Surabaya is very diverse, some of which aim to attract the attention of buyers to buy their wares, some to seduce buyers to buy their wares in large quantities, and some are used to appreciate fellow sellers and buyers.